The Abl SH2-kinase linker naturally adopts a conformation competent for SH3 domain binding - Chen, Shugui (Cold Spring Harbor Laboratory Press, 2007)
The core of the Abelson tyrosine kinase (c-Abl) is structurally similar to Src-family kinases where SH3 and SH2 domains pack against the backside of the kinase domain in the down-regulated conformation. Both kinase families depend upon intramolecular association of SH3 with the linker joining the SH2 and kinase domains for suppression of kinase activity. Hydrogen deuterium exchange (HX) and mass spectrometry (MS) were used to probe intramolecular interaction of the c-Abl SH3 domain with the linker in recombinant constructs lacking the kinase domain. Under physiological conditions, the c-Abl SH3 domain undergoes partial unfolding, which is stabilized by ligand binding, providing a unique assay for SH3:linker interaction in solution. Using this approach, we observed dynamic association of the SH3 domain with the linker in the absence of the kinase domain. Truncation of the linker before W254 completely prevented cis-interaction with SH3, while constructs containing amino acids past this point showed SH3:linker interactions. The observation that the Abl linker sequence exhibits SH3-binding activity in the absence of the kinase domain is unique to Abl and was not observed with Src-family kinases. These results suggest that SH3:linker interactions may have a more prominent role in Abl regulation than in Src kinases, where the down-regulated conformation is further stabilized by a second intramolecular interaction between the C-terminal tail and the SH2 domain.